The Influence of School Culture, Prosperity and Job Satisfaction on Primary School Teacher Performance - Wahdati, Anisa Kusuma; Slamet, Achmad; Hudallah, Noor (Educational Management, 2019)
Teacher performance will be optimal, if it id supported by school culture, prosperity and teacher job satisfaction. The low productivity of teachers is suspected by the monotonous school culture, lack of prosperity resulting in teacher dissatisfaction. This research was conducted to determine the influence of school culture and prosperity on job satisfaction and the influence of school culture, prosperity and job satisfaction on teacher performance. This study uses primary data through the distribution of questionnaires to respondents. The sample in the study consists of 62 respondents. The data obtained is processed using descriptive analysis and quantitative statistical analysis. Quantitative analysis uses multiple regression analysis. The results of the regression analysis show that the direct influence of prosperity on performance is 0.044. The indirect influence of prosperity variables on performance through job satisfaction was obtained 0.233. Direct influence on performance is -0,356. The indirect influence of school culture on performance (0.136) is greater than the direct influence of school culture on performance (-0.356). It means that job satisfaction mediates the influence of school culture on work performance and satisfaction mediating prosperity towards performance. It shows that the need for an increase in school culture, prosperity and job satisfaction significantly influences teacher performance, both individually and collectively. It shows that to improve teacher performance there needs to be a school culture, prosperity and job satisfaction.